La historiografía griega / Arnaldo Momigliano ; traducción castellana de José Martínez Gázquez - Martínez Gázquez, José; Momigliano, Arnaldo (1908-1987) (Crítica/Historia ; 30)
Bibliografía: p. 287-293. Índices